Pengaruh Motivasi Intrinsik dan Intensitas Belajar Mandiri terhadap Hasil Belajar Matematika Siswa SMP Berbasis Pesantren - Faturohman, Ikhsan; Fazriansyah, Muh. Fajar (Papanda, 2025)
This study aims to examine the influence of intrinsic motivation on mathematics learning outcomes of junior high school students in a pesantren-based school and to analyze the role of self-directed learning intensity in strengthening that influence. A quantitative approach with a survey method was employed. The sample consisted of 30 eighth-grade students of SMP Al Halim, West Java, selected using purposive sampling. The research instruments included an intrinsic motivation questionnaire (adapted from the MSLQ) and a self-directed learning intensity questionnaire (adapted from verified international literature), both of which were validated prior to use. Data were analyzed using multiple linear regression to assess the contribution of each variable to students’ mathematics learning outcomes. The results indicated that both intrinsic motivation and self-directed learning intensity had a significant positive effect on mathematics learning outcomes (p < 0.05). Simultaneously, the two independent variables explained 55.6% of the variation in students’ mathematics achievement (R² = 0.556), while the remaining 44.4% was influenced by other factors beyond the scope of this study. These findings suggest that students with strong internal motivation and consistent independent study habits tend to achieve better academic performance in mathematics. The implications of this research highlight the importance of instructional strategies that not only address cognitive aspects but also foster intrinsic motivation and promote independent learning habits, particularly in pesantren-based educational environments.